Preop endovascular embolization in juvenile nasal angiofibroma management - M. V. Nersesyan; S. B. Yakovlev; S. R. Arustamyan; E. Yu. Bukharin; A. V. Bocharov; D. N. Kapitanov; V. A. Cherekaev; A. Yu. Lubnin; G. V. Danilov (Опухоли головы и шеи, 2018)
Introduction. Juvenile nasal angiofibroma (JNA) is an aggressively expanding fibro-vascular benign tumor, which occurs in male adolescents. Surgical management of JNA is considered as one of the most difficult in rhinology, because it very often has accompanied with profuse, streaming bleeding. Endovascular embolization has successfully used for reducing the operative blood loss since 2000th. Nevertheless, there is no consensus in the literature about its expediently using because of complications, which may occur.Objective is to evaluate the effectiveness of selective angiography and endovascular embolization in reducing bleeding when removal of JNA of different stages.Materials and methods. In the N.N. Burdenko National Medical Research Center of Neurosurgery 134 patients with JNA had been treated surgically.Results. 110 patients with JNA, who underwent embolization, managed to perform total, subtotal or partial devascularization of the tumor. Total devascularization was achieved in JNA blood supply variant only from the external carotid artery (ECA) system from 1 or 2 sides  (in primary patients or in patients who had not previously been embolized) (n = 39); subtotal devascularization, if the blood supply was carried out from the ECA system, internal carotid artery (ICA) on the 1 side (n = 52) and partial, if there was blood supply from the ECA and significant from the ICA system from 2 sides (in patients with relapse after previous embolization with microspirals or the ECA ligations from 1 or 2 sides, as well as with giant JNA (n = 19). Since the vast majority of patients admitted to our clinic were previously operated on, and JNA blood supply in relapses was more pronounced, we performed the comparison of the degree of tumor devascularization depending on its blood supply in primary patients and patients with relapse. It turned out, as could be expected, that with the primary JNA often managed  to execute a total devascularization than with JNA with continued increase, the difference was statistically significant (p = 0.009).Conclusion. It accurately proved that embolization decreases intraoperative blood loss and reduce surgical risks even in later stages JNAs  (r = –0,51, p <10–7). Ligation of ECA as well as proximal occlusion of its branches leads to rapid reconstruction blood supply from ICA and inability of its embolization if recurrence of JNA occurs.